Authority of Judicial Bodies in Settling Tax Disputes in Indonesia - Gojali, Akhmad; Kantikha, I Made; Markoni; Nardiman (International Journal of Science and Society, 2025)
Tax is the main source of state revenue. Since 1984, tax collection in Indonesia has adopted a self-assessment system. In the practice of tax collection, disputes often occur between the Tax Authorities and Taxpayers regarding differences in the calculation of tax payable. The judicial body authorized to handle tax disputes in addition to the Tax Court, can also be resolved in other courts. The problems that arise are what causes tax disputes and how is the authority of the judicial body in resolving tax disputes. This study aims to analyze the authority of the judicial body in resolving tax disputes using the normative legal method. The results of the study show that tax disputes occur because there are differences of opinion between Taxpayers and the Tax Authorities in a legal and/or evidentiary manner. The Tax Court is only authorized to resolve disputes over Tax Authorities' Decisions and tax collections that can be appealed/lawsuited. Tax disputes related to Tax Authorities' Decisions that are detrimental to Taxpayers that are not specifically regulated are resolved in the State Administrative Court, while tax collection disputes in the form of hostage-taking of Taxpayers and third-party goods that are confiscated are the authority of the District Court. In conclusion, the authority to resolve tax disputes is not only resolved in the Tax Court, but also has the authority of the State Administrative Court and the District Court.